Evaluating forest degradation, deforestation, and reforestation in Boeny and DIANA: Current efforts and future opportunities - Ferdinand Peters; Andreas Kempe; Daniel Kübler; Sven Günter; Stefan Neumeier (Johann Heinrich von Thünen-Institut, 2024)
Madagascar's forests are known for their rich biodiversity, and they are home to numerous endemic plant and animal species. However, these ecosystems face significant threats from human activities, leading to deforestation and forest degradation. Effective conservation efforts must focus on both protecting the remaining natural forests and restoring those already destroyed. To address these challenges, the Thünen Institute of Forestry, in collaboration with the German Society for International Cooperation (GIZ), conducted the project "Analysis of forest management and reforestation potential in the regions of Boeny and DIANA in Madagascar" (AFOB). The project analysed deforestation and forest degradation along with their drivers, and evaluated the success of reforestation programs implemented over the past decades. These past programs sought to foster sustainable charcoal production practices, thereby reducing reliance on natural forests. To achieve these objectives, we used a spatial analysis approach that relied on open-access remote sensing data products. For natural forests, we identified when and where potential forest degradation and deforestation occurred and demonstrated forest fragmentation dynamics, differentiating between protected and non-protected areas. Our findings revealed that between 2000-2023, deforestation and forest degradation have increased substantially, with degradation having been a more significant issue in the past than previously understood. Key drivers include the conversion of forests into agricultural land, fire, illegal charcoal production, and the illegal extraction of valuable timber. We showed that over the last two decades, cropland has expanded significantly, with an even faster rate of increase in recent years. Our findings suggest that deforestation and forest degradation should be viewed as distinct but interrelated threats, each driven by different underlying processes that require tailored strategies, respectively. In the reforestation areas, crown cover was initially low during the first rotation but showed an upward trend over the analysed period. However, more than half of the plots did not develop crown cover exceeding 20%, suggesting that they did not reach their full ecological potential. In a subsequent analysis, we found that environmental factors, such as topography and soil, consistently influenced crown cover development across regions and programs, while the influence of socio-economic factors varied by program and region. However, these factors had only a weak overall influence on crown cover. In contrast, our analysis suggested that unaccounted plot-level factors, which we could not include due to data limitations, had a significant impact on crown cover variation. These factors could potentially include initial planting densities, survival rates, presence of remnant vegetation, fire management, and management objectives of the landowner, though their exact nature remains speculative. This indicates that a uniform reforestation approach is ineffective; instead, site-specific adaptive management is crucial for success. In an additional analysis, we identified suitable areas with potentially high growth rates for reforestation, which can guide future restoration initiatives with a stronger focus on site-specific planning. The insights gained from the AFOB project will assist GIZ in planning and implementing targeted reforestation and conservation initiatives, ultimately supporting the preservation of Madagascar's unique ecosystems and maintaining ecological integrity. – – Die Wälder Madagaskars sind für ihre hohe biologische Vielfalt bekannt und beherbergen zahlreiche endemische Pflanzen- und Tierarten. Diese Ökosysteme sind jedoch stark durch menschliche Aktivitäten bedroht, die zu Abholzung und Walddegradierung führen. Wirksame Naturschutzmaßnahmen müssen sich sowohl auf den Erhalt der verbleibenden natürlichen Wälder als auch auf die Wiederherstellung bereits zerstörter Wälder konzentrieren. Zur Bewältigung dieser Herausforderungen führte das Thünen-Institut für Waldwirtschaft in Zusammenarbeit mit der Deutschen Gesellschaft für Internationale Zusammenarbeit (GIZ) das Projekt 'Analyse des Waldbewirtschaftungs- und Wiederaufforstungspotenzials in den Regionen Boeny und DIANA in Madagaskar (AFOB)" durch. Das Projekt analysierte die Entwaldung und Walddegradierung sowie deren Ursachen und den Erfolg von Wiederaufforstungsprogrammen, die in den letzten Jahrzehnten durchgeführt wurden. Diese Programme zielten darauf ab, nachhaltige Praktiken für die Holzkohlegewinnung zu fördern und so die Abhängigkeit von natürlichen Wäldern zu reduzieren. Um die Projektziele zu erreichen, verwendeten wir einen räumlichen Analyseansatz, der auf frei zugänglichen Fernerkundungsprodukten basierte. Für Naturwälder haben wir ermittelt, wann und wo potenzielle Walddegradierung und Entwaldung erfolgten und die Dynamik der Waldfragmentierung aufgezeigt. Dabei haben wir zwischen geschützten und nicht geschützten Waldgebieten unterschieden. Unsere Ergebnisse zeigen, dass Entwaldung und Walddegradierung zwischen 2000 und 2023 erheblich zugenommen haben, und dass die Degradierung in der Vergangenheit ein größeres Ausmaß hatte als bisher angenommen. Zu den Hauptursachen gehören die Umwandlung von Wäldern in landwirtschaftliche Flächen, Waldbrände, illegale Holzkohleproduktion und der illegale Einschlag wertvoller Bäume. Wir konnten zeigen, dass sich die Ackerflächen in den letzten zwei Jahrzehnten deutlich ausweiteten, wobei die Zuwachsrate in den letzten Jahren nochmals anstieg. Unsere Ergebnisse deuten darauf hin, dass Entwaldung und Walddegradierung als unterschiedliche, aber miteinander verknüpfte Bedrohungen betrachtet werden sollten, denen jeweils spezifische Prozesse zugrunde liegen, die angepasste Strategien erfordern. In den Wiederaufforstungsflächen war die Überschirmung während der ersten Umtriebszeit zunächst gering, zeigte aber über den Untersuchungszeitraum hinweg eine steigende Tendenz. Auf mehr als der Hälfte der Flächen blieb der Überschirmungsgrad jedoch unter 20 %, was darauf hinweist, dass das volle ökologische Potenzial nicht ausgeschöpft wurde. Eine weitergehende Analyse zeigte, dass Umweltfaktoren wie Topografie und Bodentypen die Entwicklung des Überschirmungsgrads in allen Regionen und Programmen ähnlich beeinflussten, während der Einfluss sozioökonomischer Faktoren je nach Programm und Region variierte. Diese Faktoren hatten jedoch insgesamt nur einen geringen Einfluss auf die Überschirmung. Im Gegensatz dazu deuten unsere Ergebnisse darauf hin, dass flächenspezifische kleinräumige Faktoren, die wir aufgrund eingeschränkter Datenverfügbarkeit nicht in die Analyse einbezogen werden konnten, signifikant zur Variation der Überschirmung beitrugen. Zu diesen Faktoren, deren genaue Natur spekulativ bleibt, könnten z.B. anfängliche Bepflanzungsdichten, Überlebensraten, Vorhandensein von Restvegetation, Feuermanagement und Bewirtschaftungsziele des Landbesitzers gehören. Dies deutet darauf hin, dass ein einheitlicher Wiederaufforstungsansatz ineffektiv ist; für den Erfolg ist vielmehr ein standortspezifisches, adaptives Management entscheidend. In einer zusätzlichen Analyse haben wir geeignete Gebiete mit potenziell hohen Wachstumsraten für die Wiederaufforstung identifiziert, die als Orientierungshilfe für künftige Wiederherstellungsinitiativen dienen können, in denen standortspezifische Planung eine größere Rolle spielt.
urn:nbn:de:gbv:253-202410-dn068880-1
Keywords: 630; deforestation; forest degradation; remote sensing; reforestation; forest landscapes; Entwaldung; Walddegradierung; Fernerkundung; Wiederaufforstung; Waldlandschaften